2002
DOI: 10.1097/00001665-200207000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Auditory ERPs Reveal Brain Dysfunction in Infants With Plagiocephaly

Abstract: It is suspected that the developmental delay in school-aged children diagnosed as infants suffering from plagiocephaly is caused by the modification of the skull form. To detect possible cognitive impairment in these children, we examined auditory ERPs to tones in infant patients. The infants with plagiocephaly exhibited smaller amplitudes of the P150 and the N250 responses to tones than healthy controls. Differences between the patients and control subjects indicate that already at this early age the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 18 publications
0
53
1
1
Order By: Relevance
“…Currently, however, consensus appears to favour the concept that these children are, in fact, at an increased risk for the development of neurocognitive deficits (2,3,9,10). Studies involving functional testing measures, such as positron emission tomography scans (11) and auditory event-related potentials (12), support this contention by demonstrating measurable brain activity changes in children diagnosed with SSC. Other studies attempting to quantify and characterize these neurocognitive deficits have noted the following areas of concern for some children with SSC: speech and language (4,13); motor development (5,14); and attention, planning, processing speed and visual spatial skills (15).…”
Section: Discussionmentioning
confidence: 93%
“…Currently, however, consensus appears to favour the concept that these children are, in fact, at an increased risk for the development of neurocognitive deficits (2,3,9,10). Studies involving functional testing measures, such as positron emission tomography scans (11) and auditory event-related potentials (12), support this contention by demonstrating measurable brain activity changes in children diagnosed with SSC. Other studies attempting to quantify and characterize these neurocognitive deficits have noted the following areas of concern for some children with SSC: speech and language (4,13); motor development (5,14); and attention, planning, processing speed and visual spatial skills (15).…”
Section: Discussionmentioning
confidence: 93%
“…These measures have not previously been demonstrated in normal term infants at home, although one study has shown the protective effect of a regimen of varied sleeping positions, including prone, in preventing dolichocephaly in premature infants in a hospital setting. 38 Although no objective measure of developmental 15,23,30,[33][34][35] likely delays are a contributory factor in the development of head shape asymmetry. It has been shown that supine sleepers achieve certain milestones later than prone sleepers, although they catch up by 18 months, 18,36 and it is possible that the reported developmental delays were related to this trend.…”
Section: Discussionmentioning
confidence: 99%
“…10,21,28,30,63 Multiple reports over the past decade have pointed to links between PP and abnormal ophthalmological findings, auditory processing, and motor development. 4,10,25,27,28,35,44,47,62,63,68 Two case-controlled studies, by Speltz et al 63 and Fowler et al, 21 found significant variability in gross motor development and body tone. However, almost none of these studies account for sleep position and many have problems with their design, suggesting that there are probably other factors at play.…”
Section: Established Risk Factorsmentioning
confidence: 99%